Zoledronic Acid Potentiates mTOR Inhibition and Abolishes the Resistance of Osteosarcoma Cells to RAD001 (Everolimus): Pivotal Role of the Prenylation Process - Gatien Moriceau; Benjamin Ory; Laura Mitrofan; Chiara Riganti; Frédéric Blanchard; Régis Brion; Céline Charrier; Séverine Battaglia; Paul Pilet; Marc G. Denis; Leonard D. Shultz; Jukka Mönkkönen; et al. (2010)
Abstract Despite recent improvements in therapeutic management of osteosarcoma, ongoing challenges in improving the response to chemotherapy warrants new strategies still needed to improve overall patient survival. In this study, we investigated in vivo the effects of RAD001 (Everolimus), a new orally available mTOR inhibitor, on the growth of human and mouse osteosarcoma cells either alone or in combination with zoledronate (ZOL), an anti-osteoporotic drug used to treat bone metastases. RAD001 inhibited osteosarcoma cell proliferation in a dose- and time-dependent manner with no modification of cell-cycle distribution. Combination with ZOL augmented this inhibition of cell proliferation, decreasing PI3K/mTOR signaling compared with single treatments. Notably, in contrast to RAD001, ZOL downregulated isoprenylated membrane-bound Ras concomitantly with an increase of nonisoprenylated cytosolic Ras in sensitive and resistant osteosarcoma cell lines to both drugs. Moreover, ZOL and RAD001 synergized to decrease Ras isoprenylation and GTP-bound Ras levels. Further, the drug combination reduced tumor development in two murine models of osteoblastic or osteolytic osteosarcoma. We found that ZOL could reverse RAD001 resistance in osteosarcoma, limiting osteosarcoma cell growth in combination with RAD001. Our findings rationalize further study of the applications of mTOR and mevalonate pathway inhibitors that can limit protein prenylation pathways. Cancer Res; 70(24); 10329–39. ©2010 AACR.